Salivary endocannabinoids as mediators in the relationship between omega-6 and omega-3 fatty acid ratio intake from highly-processed foods and anthropometric markers of health in women. (17th February 2020) - Tarragon, Ernesto; Bindila, Laura; Zimmer, Patrick; Lutz, Beat; Meyer, Jobst
Abstract: Data suggest that a high ω6 to ω3 ratio (ω6:ω3) contributes to obesity. Highly processed foods are a common source of high ω6:ω3 and have also been associated with increased cardiovascular risk. We hypothesised that salivary endocannabinoids (eCBs) act as a mediator between ω6:ω3 from highly processed foods and anthropometric markers of cardiovascular risk. Finally, we explored sex differences on these parameters. Participants filled a self-report intake frequency inventory. Body measurements were registered, and fasted saliva was collected and analysed using LC/MRM. Overweight subjects consuming more highly processed foods, but not those consuming more whole foods, presented an increased ω6:ω3 and salivary eCB levels. Also, the ω6:ω3 ratio in participants consuming highly processed but not whole foods predicted eCB levels in overweight women. Finally, we show that salivary eCBs correlate with body composition in women only. Our study shows that the food source has a differential impact on physiological and behavioural aspects of food intake. Graphical Abstract: